Administrative law for public managers - Rosenbloom, David H. (Routledge, 2023)
This book focuses on the essentials that public administration students and public managers should know about administrative law-why we have administrative law, the constitutional structure for and constraints on public administration, and administrative law's formats for rulemaking, adjudication, enforcement, transparency, and judicial and legislative review of administrative activity. Author David Rosenbloom views administrative law from the perspectives of administrative practice, rather than lawyering, with an emphasis on how various administrative law provisions promote their underlying goals of improving the fit between public administration and U.S. democratic-constitutionalism. Organized around federal administrative law while including material on state practices where appropriate, the book explains the essentials of administrative law clearly and accurately, in non-technical terms, and in sufficient depth to provide readers with a sophisticated, lasting understanding of the subject matter. Written in a reader-friendly style, Administrative Law for Public Managers, 3rd Edition is an ideal introduction to the subject for students in public administration, public policy, American government, law and practicing public managers alike"--